Do Maranhão para o mundo e vice-versa: Ciência sem Fronteiras como política de internacionalização do IFMA - Almeida, Simone Maranhão Costa (2016)
The present dissertation examines the political, scientific and educational meanings of the Science without Borders (SwB) Program at the Federal Institute of Education, Science and Technology of Maranhão (IFMA), between 2012 and 2015. This way, we demonstrated the contradictions and mediations in the evolution of higher education history related to the internationalization process in Brazil, up to the recent SwB – a federal academic mobility program, launched in 2011. We also highlighted the origin of this demand, its structuring concepts and main actors. Educational policies are not, by far, neutral or unilateral. On the contrary, in times of intense globalization, they are based on the defense of lucrative applied knowledge, mass accessibility, precarious expansion and internationalization subjected to the developed countries. The Federal Institutes are inserted into the confluence of this reality, trying to meet the demands of higher and professional education. Therefore, we tried to apprehend the meanings attributed by IFMA to join the SwB Program, in aspects such as: educational democracy, research network, teaching quality, extension activities, and integration of the international dimension to institutional management, among others. We analyzed the materialization of this national action into local context by using institutional documents, interviews with leaders and questionnaires applied to the SwB students. The results pointed that SwB intensified the internationalization process at the Institution in a disorganized manner. For the students, the main contributions were on the personal, cultural and linguistic levels. However, the challenges to internationalize IFMA were, for example, the dependency of government initiatives, the priority given to agreements with North hemisphere countries, the high cost of academic mobility, the low level of foreign language proficiency among staff and students, the difficulties to attract researchers, and, above all, the passive and disarticulated way internationalization still happens there.